2012
DOI: 10.1111/j.1472-765x.2011.03196.x
|View full text |Cite
|
Sign up to set email alerts
|

Growth of Pseudomonas fluorescens in modified atmosphere packaged tofu

Abstract: Aims:  The objective was to study the growth of Pseudomonas in a food product (tofu) where it typically occurs as a spoilage organism, and when this product is stored under modified atmosphere. Methods and Results:  A Pseudomonas strain was isolated from the endogenous microflora of tofu. Tofu was inoculated with the strain, packaged in different gas conditions (air, 100% N2, 30% CO2/70% N2 or 100% CO2) and stored under refrigerated conditions. Microbial loads and the headspace gas composition were monitored d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…() showed that in 30% CO 2 /70% N 2 MAP, some Pseudomonas strains could grow in large quantities in tryptone soy broth. This result is also similar to that of Stoops, Maes, Claes, and Van () who studied the growth of Pseudomonas fluorescens in tofu stored in MAP. By 28 days of storage in MAP, Pseudomonas remained the main spoilage organism in roast chicken, and its relative abundance increased by approximately 40%.…”
Section: Resultssupporting
confidence: 89%
“…() showed that in 30% CO 2 /70% N 2 MAP, some Pseudomonas strains could grow in large quantities in tryptone soy broth. This result is also similar to that of Stoops, Maes, Claes, and Van () who studied the growth of Pseudomonas fluorescens in tofu stored in MAP. By 28 days of storage in MAP, Pseudomonas remained the main spoilage organism in roast chicken, and its relative abundance increased by approximately 40%.…”
Section: Resultssupporting
confidence: 89%
“…Both insect species were also colonised by OTUs representing members of Pseudomonas. Pseudomonads are important spoilage organisms in meat, fish, eggs, milk, vegetables and tofu (Masson et al, 2002;Stoops et al, 2012). Results of the culture-independent analyses showed that fresh insects contained a variety of potential spoilage bacteria.…”
Section: ) and The Bark Beetle (Dendroctonus Rhizophagus) (Moralesmentioning
confidence: 97%
“…P. fluorescens isolated from sea bream stored aerobically in Greece market at 0°, 10°, and 20°C and modified-atmosphere packaging (MAP) conditions (40% CO 2 -30% N 2 -30% O 2 ) (Tryfinopoulou et al 2002). An investigation in Belgium has confirmed Fasolato et al (2018) NS not specified the growth of P. fluorescens in tofu packed in modified conditions and showed that some strain can survive under 100% CO 2 (Stoops et al 2012). The postpasteurization contamination (PPC) of high temperature, short time-pasteurized fluid milk with P. fluorescens continues to be an issue with processor defects like lower flavor scores, coagulation, and fruity fermented milk (Reichler et al 2018).…”
Section: Pseudomonas Fluorescens As a Food Spoilermentioning
confidence: 95%